The Impact of The Idea of Rangga (Masculinity) Towards Domestic Violence in The Maja Labo Dahu Culture: Study of Sociology and Social Sciences Education - ZM, Hamidsyukrie; Syafruddin, Syafruddin; Handayani, Nurlaili (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The purpose of the study was to describe the relationship between the idea of Rangga (masculinity) in the Maja Labo Dahu culture of the Bima people based on sociological studies and social education. The approach used in the research is a qualitative approach with ethnographic methods. Data were collected through observation, interviews, and documents. The results showed that several religious doctrines are directly related to preserving the idea of male dominance over women, which in turn allows the formation of a discourse of violence in the Bima Maja Labo Dahu cultural community. The doctrines are related to (1) the meaning of the origin of the creation of women from men and for men; (2) the meaning of Adam's expulsion from heaven caused by women; (3) the meaning of Rangga for men in gender roles as a figure who protects and dominates women; and (4) the meaning of wife beating as something legitimized by community culture. This understanding and meaning tend to position men as a figure who bears the idea of Rangga, masculine, male, which is then legitimized as a protector and dominator of women. Women are controlled, subordinated, and used as property. So that the impact of Rangga's thinking on Maja Labo Dahu Culture not only resulted in women becoming victims of domestic violence but also women were not given ample space to contribute to improving community growth and economy.